Microbiological contamination of shell eggs produced in conventional and free-range housing systems. (January 2015) - Parisi, M.A.; Northcutt, J.K.; Smith, D.P.; Steinberg, E.L.; Dawson, P.L.
Abstract: The present study was conducted to determine microbiological contamination of free-range and conventional chicken eggs produced under controlled conditions. Eighty-four certified Salmonella -free Bovan Brown chicks (age 2 days) were grown in 6 separate floor pens until age 16 weeks, and then moved into 3 conventional battery cages (BC) or 3 free-range (FR) housing systems. Total aerobic microorganisms and Enterobacteriaceae on egg shell surfaces were enumerated weekly when the hens were 20–27 weeks of age ( N  = 535 and N  = 541 for BC and FR, respectively). Prevalence of Salmonella and Campylobacter were determined on crushed egg shells ( N  = 212 and N  = 176, respectively) and in feces ( N  = 36 and N  = 30, respectively) collected from hens at 24 and 28 weeks of age. Counts of total aerobic microorganisms recovered from BC and FR eggs ranged from 5.0 to 6.0 log10  CFU/mL. Numbers of Enterobacteriaceae averaged 1.0 log CFU/mL higher (90% greater) on FR eggs than on eggs from BC hens. Salmonella was not detected on any of the eggs collected from BC hens (0/212), but prevalence on eggs collected from FR hens was 2.36% positive (5/212). Prevalence of Campylobacter recovered from eggs collected from FR (26.1% positive or 46 out of 176 positive) was significantly higher ( P  ≤ 0.0001) than the prevalence of Campylobacter recovered from eggs from BC hens (7.4% positive or 13 out of 176 positive). These data demonstrate that FR eggs, where hens have more contact with eggs after oviposition, have greater microbiological contamination on the egg shell surface than eggs produced in the BC cage systems. Highlights: A side-by-side chicken egg comparison study of different production environments was performed. Free-range eggs had higher counts of Enterobacteriaceae than battery cage eggs. Free-range eggs had higher prevalence of Salmonella and Campylobacter spp. than battery cage eggs. Consumers should not assume that free-range eggs are microbiologically safer than battery cage eggs.